STUDY OF LIPID PROFILE IN SUBCLINICAL HYPOTHYROIDISM - DR.SHIVALEELA M BIRADAR; DR.SANTOSH R PATIL (International Journal of Pharma and Bio Sciences, 2015)
Background: There is growing evidence that subclinical hypothyroidism is associated with increased risk of atherosclerosis and cardiovascular diseases. The relationship between subclinical hypothyroidism and lipid profile has been widely investigated, but the findings remain controversial. Objectives: This study was done to find out the association between subclinical hypothyroidism and lipid profile. Materials and Methods: Case control study was done taking 30 Subclinical hypothyroidism patients as cases and 30 age and sex matched healthy euthyroid subjects as controls. Results: The results showed a significant increase in total cholesterol, LDL cholesterol, triglycerides (p< 0.001) and a significant decrease (p<0.001) in HDL cholesterol in subclinical hypothyroidism cases as compared to controls. Conclusion: It can be concluded that Subclinical hypothyroidism cases exhibit an atherogenic serum lipid profile pattern which increases the risk of atherosclerosis and cardiovascular diseases. Therefore the routine assessment of serum lipid profile if done early in subclinical hypothyroidism would be helpful to prevent or reduce the risk of development of atherosclerosis and its associated cardiovascular complications.